Sistem Penilaian Rapot di Sekolah Menengah Atas Yadika 2 - Purnama, Gunadi; Putro, Endi (Teknik dan Ilmu Komputer, 2014)
Report Cards in Yadika 2 high school were prepared by homeroom teacher. Report card grades are the grade accumulated in each subject provided by each subject teacher. The report card preparation was done manually and not well documented in a system. The preparation required a relatively long time and held the risks of document loss or damage. The grading system at SMA Yadika was designed to anticipate these risks. The objective of this system was to facilitate homeroom teachers to prepare the report cards and to compile students grades in a system. The time required to prepare the report cards was reduced and the students scores were well documented. THe system design used survey research methodology, UML, usecase diagram and activity diagram. Students grades that had been inputted were stored in a database accesible to teacher, homeroom teachers, students, and administrator.ÃÂ Keyword: Grades, Students, Report Card